614.8 PRINCIPLES OF ORGANIZING MATERIAL AND TECHNICAL SUPPORT IN EMERGENCY SITUATIONS - Egamberdiyev, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Today, due to the impact of humanity on ecology and the environment, climate change has emerged in many regions, and the number of emergencies is increasing. As a result, serious damage is being caused to people's lives and health, the property of legal and physical entities, and the environment. This necessitates taking preventive measures against emergencies and organizing material and technical support to mitigate the consequences with minimal losses in case they occur. During the research, normative and legal documents and literature related to the field were analyzed, and national and international experiences in organizing material and technical support during emergencies were studied, and recommendations for improving this system were developed.